1997
DOI: 10.1097/00005344-199703000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Dependent Relaxation Is Not Uniformly Impaired in Chronic Heart Failure

Abstract: Abnormalities of vasomotor tone are characteristic of heart failure. This study was designed to assess the effects of chronic heart failure on endothelium-dependent relaxation in both large conduit arteries and small resistance vessels and to determine whether or not impaired nitric oxide (NO) production is involved. Segments of pulmonary artery (PA), abdominal aorta (AA), and small mesenteric artery (MA) were harvested from rats with heart failure resulting from coronary artery ligation and from sham-operated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 14 publications
2
20
0
3
Order By: Relevance
“…In agreement with other studies (Baggia et al, 1997;Bauersachs et al, 1999Bauersachs et al, , 2002Ceiler et al, 1999;Schä fer et al, 2003), we found no impairment of the endothelium-independent relaxation produced by SNP following infarction. However, we found impairment in the endothelium-dependent relaxation mediated by ACh in the tail vascular beds in Inf rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with other studies (Baggia et al, 1997;Bauersachs et al, 1999Bauersachs et al, , 2002Ceiler et al, 1999;Schä fer et al, 2003), we found no impairment of the endothelium-independent relaxation produced by SNP following infarction. However, we found impairment in the endothelium-dependent relaxation mediated by ACh in the tail vascular beds in Inf rats.…”
Section: Discussionsupporting
confidence: 93%
“…Impairments in endothelium-dependent relaxation have also been reported in patients with cardiovascular disease and chronic heart failure (Belardinelli, 2001;Annuk et al, 2003;Linke et al, 2003). Studies in different vessels using the rat infarction model for heart failure show either reductions or no changes in endothelial dependent relaxation, at different times after infarction (Teerlink et al, 1993;Baggia et al, 1997;Bauersachs et al, 1999Bauersachs et al, , 2002Ceiler et al, 1999;Indik et al, 2001;Annuk et al, 2003). Possibly, the endothelial dysfunction observed in heart failure may depend on its stage and the type of vessels studied (Fang and Marwick, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the role of NO in the regulation of vasomotor tone in MI-induced LV dysfunction in rats indicate that between 4 and 16 wk after infarction, acetylcholine-or ADP-induced NOmediated relaxation of systemic conductance arteries (4,40,43,53,57) and resistance vessels (13) is reduced, although this is not an unequivocal finding (2,6). In contrast, basal NO production is maintained in systemic conductance arteries (2,43) and in resistance vessels in various regional vascular beds in vivo (6,10,13,21).…”
mentioning
confidence: 99%
“…In comparison, a normal acetylcholine-induced relaxation with reduction of basal NO release was found in small mesenteric arteries from this rat HF model. 6,7 Conflicting data exist with regard to eNOS expression and activity in human beings with chronic HF. Increased cardiac expression of eNOS, however, with no increased eNOS activity, was found in end-stage human heart failure.…”
mentioning
confidence: 99%